The study of hydraulic hammer device in drilling tool assembly in hydraulical rotary drilling - I. Suleimanov, R; S. Gabdrakhimov, M; Ya. Khabibullin, M; M. Zaripova, L; R. Vasilyeva, E (International Journal of Engineering and Technology, 2018)
The article presents the study of a hydraulic hammer device for rotary well drilling. The mathematical model of the hydraulic hammer device has been described and studied, the relation of the dynamic load changes on the rock-destruction tool from the principal parameters of the hydraulic hammer device have been obtained. The trial rotary boring with the use of a hydraulic hammer device in drill tool assembly has been carried out, an increase in the drilling penetration rate has been achieved by 47%.